Infant Feeding Practice of Mother attending Pediatric out Patients Department in A Tertiary Care Center (Bangladesh Journal of Child Health, 2014)
Background: Appropriate breastfeeding and complementary feeding practices are the fundamental to childrens nutrition, health and survival during the first year of life. WHO and UNICEF have articulated a global strategy for poor infant feeding practices directly and indirectly contributes to under nutrition, morbidity and mortality in infant. Objective: This study was designed to determine the breast feeding (BF) and complementary feeding (CF) practices in study population. Methodology: This descriptive cross sectional study was carried out in Pediatrics out patients department (OPD) of Shahid Surhawardy Medical College and Hospital, from January 2009 to December 2009. Feeding history of total 250 babies age >6 months to